Memory and learning deficiencies in Parkinson’s disease: understanding cognitive challenges and interventions - Khairuddin, Tihani Husna; Azwan, Nurfarah Nadhirah; Ruhaizad, Nur Radhna Sari; Hairul Anuar, ‘Alia Nabila; Suhaimi, Nurul Syuhadah Fitri; Che Mohd Nassir, Che Mohd Nasril; Ahmed, Mohamed Ayaaz; Alaa Eldin, Amirah Hannan; Md Tajudin, Huriyyah Hamiemah; Jaffer, Usman (Global Academic Excellence (GAE), 2025)
Parkinson’s disease (PD) is a progressive neurodegenerative disorder primarily characterized by motor symptoms and cognitive impairments, particularly in memory and learning. These impairments significantly affect the patients’ quality of life and people around them. Based on the past studies, aging, genetics and environment are expected to be some of the contributing factors in Parkison’s disease. Cognitive impairments in PD commonly caused by neurochemical or structural changes in the brains, which decrease dopaminergic neurons in substantia Nigra pars compacta (SNpc). Furthermore, this paper explores various cognitive domains including memory, learning and other executive functions in order to understand the extent of impairment that is experienced by people with Parkinson’s disease. However, despite the extensive study on PD, current interventions demonstrate lack of effectiveness in eradicating the issue of cognitive deficiency especially on learning and memory impairment. Hence, the paper discusses current interventions by addressing and applying the reviewed literature, ranging from pharmacological treatments to lifestyle modifications aimed at mitigating cognitive decline. This study also provides a comprehensive overview of suggestions for future research about PD. Lastly, from Islamic perspective, there is a hadith that encourages seeking medical treatment while integrating it with spiritual practices, such as Qur’anic recitation, to alleviate cognitive impairments. Listening to, reciting, and memorizing the Qur’an have been shown to enhance concentration, promote neuroplasticity, delay cognitive aging and improve memory, which can help mitigate the effects of PD.